PERAN AGEN TERHADAP PERMINTAAN ASURANSI JIWA SYARIAH (STUDI KASUS PADA PT. ASURANSI JIWA SYARIAH BUMIPUTERA) - Dini Vientiany; Naswa Aldira Putri; Yusra Lestari Harahap; Tamlija (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The role of agents in increasing the attractiveness of sharia insurance customers is the agent's involvement in expanding the market because agents can convince customers and make them interested in joining as sharia insurance participants through direct promotions. This research is a qualitative descriptive study. Data collection used in this research was carried out through triangulation (combination) of literacy in scientific articles, journals and magazines. The results of this research indicate that the lineage of the founder of PT. Bumiputera Sharia Life Insurance is a long-established national life insurance company.